Perception of fatigue during simulated competition - Joseph, T.; Johnson, B.; Battista, R. A.; Wright, G.; Dodge, C.; Porcari, J. P.; de Koning, J. J.; Foster, C. (Medicine & Science in Sports & Exercise, 2008)
Background: Previous studies suggest that the rating of perceived exertion (RPE) increases during steady-state, open-loop exercise in proportion to the relative time to fatigue. This suggests that RPE is scalar and integrates physiological status and homeostatic disturbances.